Relationship of angiogenesis factor in synovial fluid to various joint diseases. Issue 3 (June 1983) - Brown, R A; Tomlinson, I W; Hill, C R; Weiss, J B; Phillips, P; Kumar, S
Abstract : A low-molecular-weight freely dialysable angiogenesis factor has been isolated from 49 synovial fluids obtained from patients with various joint diseases. An analysis of disease type and incidence of freely dialysable angiogenesis activity showed that the osteoarthrotic group had a significantly higher incidence than all the other groups (p = 0.0332). Angiogenesis factor has also been detected in a bound form in the retentates of fluids which gave positive results for dialysable factor. The possibility that an imbalance between carrier-bound and free factor may have a causative role in disease is discussed.